2015
DOI: 10.1007/s00705-015-2688-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of bovine viral diarrhea virus in uruguay

Abstract: Bovine viral diarrhea (BVD) affects bovine production and reproduction causing significant economic losses all over the world. Two viral species has been recognized: BVDV-1 and BVDV-2, both distributed worldwide. Recently, novel specie of BVDV named HoBi-like pestivirus was discovered. The presence of BVDV was confirmed in 1996 in Uruguay, however, does not exist until today a schedule of compulsory vaccination along the country. Serological studies with samples from all Uruguayan herds were performed during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 29 publications
2
37
1
6
Order By: Relevance
“…: Genotyping was not performed. References (I): [48,49,50,51,52]; (II): [7,43,49,52,53,54,55,56,57,58]; (III): [59,60]; (IV): [39,44,49,61,62,63,64,65,66,67,68,69,70]; (V): [49,71]; (VI): [72]. In [57] the year of virus isolation was not displayed in the study.…”
Section: Figurementioning
confidence: 99%
“…: Genotyping was not performed. References (I): [48,49,50,51,52]; (II): [7,43,49,52,53,54,55,56,57,58]; (III): [59,60]; (IV): [39,44,49,61,62,63,64,65,66,67,68,69,70]; (V): [49,71]; (VI): [72]. In [57] the year of virus isolation was not displayed in the study.…”
Section: Figurementioning
confidence: 99%
“…Understanding the genetic diversity of pestiviruses in a country is essential to the development of regional control programmes (Dubovi, ; Fulton, ). Thus far, BVDV‐1 is the most prevalent pestivirus species identified worldwide; however, the proportion of bovine pestivirus species varies by geographic region (Abe et al., ; Booth et al., ; Giammarioli, Ceglie et al ., ; Jones, Zandomeni, & Weber, ; Maya et al., ; Nagai et al., ; Weber et al., ; Workman et al., ). Brazil has several distinct geographic regions and a large agroindustry based on cattle production (IBGE, Instituto Brasileiro de Geografia e Estatística, ; USDA – FAS, United States Department of Agriculture, Foreign Agricultural Service, ).…”
Section: Introductionmentioning
confidence: 99%
“…As viruses with worldwide distribution [9], BVDV-1 and BVDV-2 have been recognized for many years in South American countries, including Brazil [14], Argentina [15], Colombia [16], Peru, Chile [17], and Uruguay [18], while the Pestivirus HoBi-like virus has currently only been identified in Argentina [19] and Brazil [20] on this subcontinent. In Uruguay, the first evidence of BVDV circulation dates from 1996 [21].…”
Section: Introductionmentioning
confidence: 99%
“…A serological study revealed that BVDV exposure is widespread in beef cattle throughout Uruguay [22]. More recently, active BVDV infections and circulating species and subtypes were explored in cattle herds with reproductive problems, and BVDV-1a was revealed as the predominant species/ subtype, followed by BVDV-1i and BVDV-2b [18].…”
Section: Introductionmentioning
confidence: 99%